2021
DOI: 10.1007/s00414-021-02588-x
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin 1 and 3 as local vitality markers in mechanical and thermal skin injuries

Abstract: Assessment of the vitality of an injury is one of to the main tasks in daily forensic casework. Aquaporins belong to the family of water channels. They enable the transport of water and of small molecules like glycerol through biological channels. So far, 13 classes of aquaporins are identified in vertebrates. The classical aquaporin channels 1, 2 and 4 are only permeable for water. The aquaporin channels 3, 7, 9 and 10 are also called aquaglycerolporins since they can also transport glycerol. Aquaporin 3 is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 10 publications
2
8
0
1
Order By: Relevance
“…There was no correlation between AQP3 expression and age, sex, body mass index, duration of agony, and post-mortem interval. For AQP1, there were no differences between injured and uninjured skin (45).…”
Section: Skin Injuriesmentioning
confidence: 81%
“…There was no correlation between AQP3 expression and age, sex, body mass index, duration of agony, and post-mortem interval. For AQP1, there were no differences between injured and uninjured skin (45).…”
Section: Skin Injuriesmentioning
confidence: 81%
“…An increased expression of aquaporin 3 in the keratinocytes of the epidermis was described in all kinds of mechanical and trauma injuries. Aquaporin 1 does not show differences in expression between injured and uninjured skin [ 41 , 44 ]. Regarding age estimation, several authors showed the importance of AQP1 and 3, which may also be increased in dermal vessels and keratinocytes, respectively [ 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…AQP1 and 3 are also significantly enhanced in ligature marks, especially on the keratinocytes of compressed skin and in the epidermis and dermal blood vessels [ 39 , 44 ]. Recently, the expression of AQP3 has been observed in frost erythema in a case of lethal hypothermia and, therefore, it could be used as a marker of vitality [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they observed that AQP3 was expressed in antemortem ligation mark keratinocytes obtained from forensic cases' autopsies compared to intact skin. Other authors ( 73 ) also analyzed AQP1 and AQP3 in strangulation marks and examined thermal injuries, gunshot wounds, and frostbite erythema. Like the previous ones, they did not find significant differences between injured and non-injured skin about the expression of AQP1.…”
Section: Wound Characterization In Post-mortem Forensic Studiesmentioning
confidence: 99%